Foreword - Teaching Legal Writing - Chantal Morton (Legal Education Review)
The demand for universities to provide technology based teaching opportunities for students is increasing. Universities consider online teaching as having economic benefits; students see technology as facilitating their need to study flexibly, and, more importantly for this paper, the legal profession is now recognising the importance of technology in practice and calling for graduates to be technology-literate. This paper accepts that technology will be part of the pedagogical practices of the teaching of law and therefore considers how technology can be used to support a fully online offering. In this regard, the paper does not accept that the teaching methods currently used in face-to-face teaching can simply be adopted in the online environment. It argues that in order to effectively facilitate interaction and student learning in the online space, law teachers, in designing units/courses, should draw upon a range of learning theories to determine the appropriate pedagogical approach to be taken and further the concepts of ‘place’ and ‘presence’ should be considered.